Cell type specific transcriptomic differences in depression show similar patterns between males and females but implicate distinct cell types and genes - Malosree Maitra; Haruka Mitsuhashi; Reza Rahimian; Anjali Chawla; Jennie Yang; Laura M. Fiori; Maria Antonietta Davoli; Kelly Perlman; Zahia Aouabed; Deborah C. Mash; Matthew Suderman; Naguib Mechawar; et al. (2023)
Abstract Major depressive disorder (MDD) is a common, heterogenous, and potentially serious psychiatric illness. Diverse brain cell types have been implicated in MDD etiology. Significant sexual differences exist in MDD clinical presentation and outcome, and recent evidence suggests different molecular bases for male and female MDD. We evaluated over 160,000 nuclei from 71 female and male donors, leveraging new and pre-existing single-nucleus RNA-sequencing data from the dorsolateral prefrontal cortex. Cell type specific transcriptome-wide threshold-free MDD-associated gene expression patterns were similar between the sexes, but significant differentially expressed genes (DEGs) diverged. Among 7 broad cell types and 41 clusters evaluated, microglia and parvalbumin interneurons contributed the most DEGs in females, while deep layer excitatory neurons, astrocytes, and oligodendrocyte precursors were the major contributors in males. Further, the Mic1 cluster with 38% of female DEGs and the ExN10_L46 cluster with 53% of male DEGs, stood out in the meta-analysis of both sexes.